ANALYSIS OF A TRACEABILITY SYSTEM FOR PERISHABLE FOOD SUPPLY CHAINS - Zhu, Lijing; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-weight: bold; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">Food traceability has attracted great attentions due to increasing concerns over food safety and quality. This study analyzes an RFID-enabled traceability system for perishable food supply chains, which consist of an upstream supplier and a downstream retailer. The supplier delivers the RFID embedded perishable food to the retailer. The deployment of RFID enables constant monitoring of the parameters that are critical to the quality and the safety of food and therefore provides real-time food quality data. Based on the quality of food when it arrives at the retailer, the supplier sets the wholesale price and the retailer determines price markdowns, accordingly. We develop a decision-making mechanism for a perishable food supply chain when demand depends on the price, the quality, and the safety of perishable food. The optimal decisions of the participants are derived in both centralized and decentralized systems. We further propose an incentive scheme to coordinate the decentralized system. Numerical analysis is conducted to provide managerial insights in terms of RFID deployment in the perishable food supply chain.